2019
DOI: 10.3390/ijms20184547
|View full text |Cite
|
Sign up to set email alerts
|

MAPK Pathway under Chronic Copper Excess in Green Macroalgae (Chlorophyta): Influence on Metal Exclusion/Extrusion Mechanisms and Photosynthesis

Abstract: There is currently no information regarding the role that whole mitogen activated protein kinase (MAPK) pathways play in counteracting environmental stress in photosynthetic organisms. To address this gap, we exposed Ulva compressa to chronic levels of copper (10 µM) specific inhibitors of Extracellular Signal Regulated Kinases (ERK), c-Jun N-terminal Kinases (JNK), and Cytokinin Specific Binding Protein (p38) MAPKs alone or in combination. Intracellular copper accumulation and photosynthetic activity (in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…It has been recognised that besides metal exclusion/extrusion mechanisms, the main strategies by which macroalgae counteract metal excess in polluted environments are detoxification of bioavailable metals through the syntheses of chelating compounds and the inactivation of metal-mediated excess of reactive oxygen species (ROS) by the production and activities of antioxidants and antioxidant enzymes [1,2]. In green macroalgae (Ulvophyceae), metal chelation is importantly controlled by cysteine-rich compounds, among which the most important are the gene encoded metallothioneins and the enzymatically synthesised glutathione (GSH) and its poly-oligomers phytochelatins (PCs) [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been recognised that besides metal exclusion/extrusion mechanisms, the main strategies by which macroalgae counteract metal excess in polluted environments are detoxification of bioavailable metals through the syntheses of chelating compounds and the inactivation of metal-mediated excess of reactive oxygen species (ROS) by the production and activities of antioxidants and antioxidant enzymes [1,2]. In green macroalgae (Ulvophyceae), metal chelation is importantly controlled by cysteine-rich compounds, among which the most important are the gene encoded metallothioneins and the enzymatically synthesised glutathione (GSH) and its poly-oligomers phytochelatins (PCs) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The potential participation of the mitogen-activated protein kinases (MAPKs) has been proposed, but not fully confirmed [2,12]. MAPKs are serine/threonine kinases following a cascade of activations from MAPK kinase kinase (MAPKKK), MAPK kinase (MAPKK) to MAPK, thus finally inducing gene expression [1,16,17]. There are three main sub-pathways within the MAPKs, these ending in the MAPK ERK (extracellular signal regulated kinases), JNK (c-Jun N -terminal kinases), and p38 (cytokinin specific binding protein) [1,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was additionally shown that the increase in gene expression involves the mitogen-activated protein kinases (MAPKs) signaling pathway [40]. The MAPKs, JNK, ERK, and p-38 are involved in the regulation of gene expression of antioxidant enzymes such as SOD, CAT, AP, DHAR, and GR [46], photosynthetic parameters, and copper accumulation, and these MAPKs showed a crosstalk among them [47]. Thus, activation of gene expression involves CaMK, CDPK, and MAPK signaling pathways.…”
Section: Mechanisms Of Copper Tolerance In the Marine Macroalga U Comentioning
confidence: 99%